(untitled) (Revista Tópos, 2013)
No Brasil, a Ginástica Artística é uma modalidade esportiva pouco conhecida se comparada a outras como o futebol, o voleibol e o atletismo. É com a intenção de tornar sua prática acessível que este projeto vem atender as crianças da comunidade, visando oferecer-lhes uma boa qualidade de vida, com uma ocupação saudável do tempo livre e, com a vivência esportiva, promover a inclusão e a interação social, e garantir o acesso à Ginástica Artística como elemento da cultura corporal do movimento. O projeto se deu mediante uma parceria entre a Secretaria Municipal de Esportes de Presidente Prudente – SEMEPP - e a Faculdade de Ciências e Tecnologia - UNESP - Campus de Presidente Prudente, atendendo, no período de março a dezembro de 2007, oitenta e três meninas com idade a partir de quatro anos. Palavras-chave: esporte; ginástica artística; cultura corporal do movimento. ARTISTIC GYMNASTICS: A PROJECT OF LIFE Abstract In Brazil, the Artistic Gymnastics is a sporting modality little known if compared the other ones as the soccer, the volleyball and the athletics. It is with the intention of turning the practice of the accessible Artistic Gymnastics that project comes to assist the community’s children, seeking to offer them a good life quality, with a healthy occupation of the free time, and with the sporting existence to promote the inclusion and social interaction, and this way to guarantee the access to the Artistic Gymnastics as element of the corporal culture of the movement. The project felt by a partnership among SEMEPP - it would Secrete Municipal of Sports of Presidente Prudente and UNESP - University of Sciences and Technology - Campus of Presidente Prudente, assisting in the period of March to December from 2007 to eighty three girls with age starting from four years. Keywords: sport; artistic gymnastics; corporal culture of the movement.